2015
DOI: 10.1017/jfm.2015.146
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-turbulent gas-phase velocity fluctuations in homogeneous gas–solid flow: fixed particle assemblies and freely evolving suspensions

Abstract: Gas-phase velocity fluctuations due to mean slip velocity between the gas and solid phases are quantified using particle-resolved direct numerical simulation. These fluctuations are termed pseudo-turbulent because they arise from the interaction of particles with the mean slip even in ‘laminar’ gas–solid flows. The contribution of turbulent and pseudo-turbulent fluctuations to the level of gas-phase velocity fluctuations is quantified in initially ‘laminar’ and turbulent flow past fixed random particle assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
130
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 66 publications
13
130
2
Order By: Relevance
“…The flow was simulated for two resolutions; the coarsest one was given by N r = 4, N θ = 24, N φ = 48, N 1 = 88, N 2 = 68 and As a fourth validation, the pressure and viscous parts of the drag force on a sphere in the flow past a structured array of spheres were computed and compared to results obtained by Tenneti et al (2011). These authors used an immersed boundary method (second-order accurate direct forcing embedded into a pseudo-spectral computation; the same method was recently used by Mehrabadi et al (2015)). It is remarked that many variants of immersed boundary methods exist and have been validated for flows past multiple particles -see also, for example, Uhlmann (2005), Mark & van Wachem (2008) and Breugem (2012).…”
Section: Results Of Test Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow was simulated for two resolutions; the coarsest one was given by N r = 4, N θ = 24, N φ = 48, N 1 = 88, N 2 = 68 and As a fourth validation, the pressure and viscous parts of the drag force on a sphere in the flow past a structured array of spheres were computed and compared to results obtained by Tenneti et al (2011). These authors used an immersed boundary method (second-order accurate direct forcing embedded into a pseudo-spectral computation; the same method was recently used by Mehrabadi et al (2015)). It is remarked that many variants of immersed boundary methods exist and have been validated for flows past multiple particles -see also, for example, Uhlmann (2005), Mark & van Wachem (2008) and Breugem (2012).…”
Section: Results Of Test Casesmentioning
confidence: 99%
“…More recently, PR-DNS studies of turbulent flows with multiple solid fixed and moving spherical particles have occurred in the literature: studies of turbulent channel flow (Uhlmann 2008;Picano, Breugem & Brandt 2015) and homogeneous isotropic turbulence (Lucci, Ferrante & Elghobashi 2010;Mehrabadi et al 2015). In all these cases, the flow was not dilute (α 0.01) and the particle diameter was relatively large (approximately 10 wall units in the turbulent channel flows and at least 5η in the homogeneous isotropic cases).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the focus of this study is on the third approach. It has been shown that fixed particle assemblies of high Stokes number particles in PR-DNS are a good approximation to freely evolving suspensions (Xu and Subramaniam, 2010;Tenneti et al, 2011;Mehrabadi et al, 2015), because the time required for the particle configuration to change significantly is much larger than the fluid relaxation timescale.…”
Section: Analysis Of Numerical Constraintsmentioning
confidence: 99%
“…The presence of clusters then gives rise to a reduction in the drag force. We have learned from PR-DNS of freely evolving gas-solid suspensions that the rate of work done in maintaining a flow with constant mean slip between the gas and solid phases by means of a constant mean pressure gradient results in the production of velocity fluctuations in both gas and solid phases (Mehrabadi et al, 2015). Therefore, reduction in the local drag force acting on particle clusters leads to local reduction of the amount of power input to the granular temperature.…”
Section: Introductionmentioning
confidence: 99%